2015
DOI: 10.3390/ijerph120707254
|View full text |Cite
|
Sign up to set email alerts
|

Scrub Typhus Incidence Modeling with Meteorological Factors in South Korea

Abstract: Since its recurrence in 1986, scrub typhus has been occurring annually and it is considered as one of the most prevalent diseases in Korea. Scrub typhus is a 3rd grade nationally notifiable disease that has greatly increased in Korea since 2000. The objective of this study is to construct a disease incidence model for prediction and quantification of the incidences of scrub typhus. Using data from 2001 to 2010, the incidence Artificial Neural Network (ANN) model, which considers the time-lag between scrub typh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 69 publications
7
42
0
Order By: Relevance
“…The number of patients has increased to around 2,000 per year since 2001, exceeding 10,000 in 2013, and approximately 10-20 deaths have been recorded per year (Lee et al 2015;; Korea Centers for Disease Control and Prevention 2018). Similar trends have been observed in surrounding countries, such as China, Japan, and Taiwan (Ogawa et al 2002;Cao et al 2006;Lee et al 2006;Bang et al 2008;Sun et al 2017); as the incidence of Tsutsugamushi disease is closely related to climatic factors (temperature, humidity, precipitation, and wind) (Kwak et al 2015), this trend may be a result of global climate change (Ogden 2017). As part of the prevention measures to reduce the number of cases of Tsutsugamushi disease, the Korea Centers for Disease Control and Prevention have implemented nationwide surveillance of the vector chigger mites and their rodent hosts, besides collecting a wide range of information on these animals.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The number of patients has increased to around 2,000 per year since 2001, exceeding 10,000 in 2013, and approximately 10-20 deaths have been recorded per year (Lee et al 2015;; Korea Centers for Disease Control and Prevention 2018). Similar trends have been observed in surrounding countries, such as China, Japan, and Taiwan (Ogawa et al 2002;Cao et al 2006;Lee et al 2006;Bang et al 2008;Sun et al 2017); as the incidence of Tsutsugamushi disease is closely related to climatic factors (temperature, humidity, precipitation, and wind) (Kwak et al 2015), this trend may be a result of global climate change (Ogden 2017). As part of the prevention measures to reduce the number of cases of Tsutsugamushi disease, the Korea Centers for Disease Control and Prevention have implemented nationwide surveillance of the vector chigger mites and their rodent hosts, besides collecting a wide range of information on these animals.…”
Section: Discussionsupporting
confidence: 67%
“…); as the incidence of Tsutsugamushi disease is closely related to climatic factors (temperature, humidity, precipitation, and wind) (Kwak et al . ), this trend may be a result of global climate change (Ogden ). As part of the prevention measures to reduce the number of cases of Tsutsugamushi disease, the Korea Centers for Disease Control and Prevention have implemented nationwide surveillance of the vector chigger mites and their rodent hosts, besides collecting a wide range of information on these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, weather differs greatly in endemic areas. Recent studies conducted in Asian countries have demonstrated that meteorological factors are statistically related to the occurrence of scrub typhus [16][17][18][19][20][21][22]. Specifically, temperature, rainfall, humidity, sunshine, atmospheric pressure, surface temperature, and wind speed are indicated as relevant factors in reports of earlier studies.…”
Section: Discussionmentioning
confidence: 98%
“…Meteorological factors are known to affect the reproduction, development, behaviour, and population dynamics of arthropods transmitting vector-borne pathogens [13][14][15]. Recently, the relationship between meteorological factors and the number of scrub typhus cases in several Asian countries has been investigated [16][17][18][19][20][21][22]. Although no consensus has been reached, meteorological factors such as temperature and rainfall are generally believed to be associated significantly with the number of scrub typhus cases.…”
Section: Introductionmentioning
confidence: 99%
“…Jhajharia et al (2013) found increasing incidences of malaria with rising temperature in Rajasthan, India. Similarly, Kwak et al (2014Kwak et al ( , 2015 found an increase in the occurrence of malaria and the shortening of annual time of occurrence in Korea as a result of climate change. Moreover, the rise of evapotranspiration is likely to increase air humidity which itself is a factor favoring germs transmissions.…”
Section: Other Societal Implicationsmentioning
confidence: 90%